Potencial das raízes de Smilax brasiliensis Spreng. (Smilacaceae) e Herreria salsaparilha Mart. (Agavaceae) no tratamento de alterações metabólicas, induzidas por dieta em camundongos BALBc - Flávia Liparini Pereira (2013)
The plant species commonly known as salsaparrilhas are widely used in traditional medicine as "blood depurative" plants. The name salsaparrilha is given to species of different genera, especially Smilax and Herreria. The aim of this work was to evaluate the effect of two species known as salsaparrilha, Smilax brasiliensis Spreng. and Herreria salsaparilha Mart., by means of biochemical parameters in mice fed an isocaloric-high carbohydrate (HC). Plant roots were collected, dried, ground and extracted with water-alcohol solution at 80º GL. The extracts tested were obtained after complete solvent evaporation. The animals were fed HC diet or control diet (C) for 8 weeks. After this period, the HC diet was supplemented during 4 weeks with two different doses, 100 and 200 mg/Kg weight/day by the crude extract of each plant. These plants showed phenolic compounds and saponins, which have the recognized ability to decrease plasma concentrations of glucose, cholesterol and triglycerides. The animals treated with the HC fed diet had higher adiposity, adipocyte hypertrophy and higher plasma concentrations of glucose, cholesterol and triglycerides than animals treated with the C fed diet. In animals treated with crude extracts, we observed lower concentrations of glucose, cholesterol and triglyceride compared to HC group. It is concluded that crude extracts from the roots of S. brasiliensis and H. salsaparilha have potential in the prevention and treatment of dyslipidemia in a dose-dependent manner. It is suggested that the effects observed in this study are due to the presence of phenolic substances and saponin in the roots of S. brasiliensis and H. salsaparilha.